PRACTICALITY TEST: INTEGRATED AUGMENTED REALITY IN ENGLISH FOR CULINARY BOOK - Fathiyanabila Wicaksono, Nurzahra; Balti, Levandra; Pebrianti, Anggita (LPPM Universitas Muhammadiyah Muara Bungo, 2024)
This research aims to test the practicality of using Augmented Reality (AR) integrated in the book